Biopolymer mixture-entrapped modified graphene oxide for sustainable treatment of heavy metal contaminated real surface water. (April 2022) - Lee, Suhyun; Lingamdinne, Lakshmi Prasanna; Yang, Jae-Kyu; Koduru, Janardhan Reddy; Chang, Yoon-Young; Naushad, Mu.
Abstract: The surface of graphene oxide (GO) features highly reactive carboxyl, epoxy, and hydroxyl groups; however, it cannot remove negatively charged species such as anion metals. Gadolinium (Gd) ions interact strongly with anionic species such as arsenic. The incorporation of gadolinium oxide to GO facilitates the removal of anion and cation heavy metals. However, the product was practically infeasible because to the thin, friable, and light flakes. To address these flaws, a polymer combination (Sodium Alginate (SA) and Carboxymethyl Cellulose (CMC)) was employed to bind GO–Gd2 O3 into granules, the ability of which was verified to adsorb Cr(III), Pb(II), and As(V). The effective operating pH, dose, and temperature were 4.0, 1.4 g/L, and 298 K, respectively. Cr(III), Pb(II), and As(V) all had adsorption capabilities of 29.16, 158.73, and 36.77 mg/g, demonstrating gGO–Gd2 O3 as effective granules for heavy metals removal from complex aquatic environments. According to the thermodynamic data, Cr(III) and As(V) adsorptions are endothermic, but Pb(II) adsorption is exothermic. The probable sorption mechanism was thoroughly discussed. The viability of produced materials was assessed by investigating their re-usability and use in real surface water. Graphical abstract: Unlabelled Image Highlights: Syntesiszed Gd2 O3 -GO@SA-CMC granules for sustainable remediation of wastewater. gGO-Gd2 O3 demonstrates the 99% adsorptive removal of anion and cation metals. The XPS spectrum confirmed the complexation and ion-exchange mechanism of metals. Evaluated feasibility of gGO-Gd2 O3 through re-usability(4 cycles) and real water column studies.